The Amazon rainforest ecotourism industry of Napo, Ecuador. - Lemky, Kim M. K. (University of Ottawa (Canada), 1992)
The two types of ecotourists have different impacts on both the local economy and the environment. The resort ecotourists are isolated to resorts. Each night is spent in the same place and tours consist of day hikes to local Indian villages and to the primary rainforest. These tourists aid the economy less than budget ecotourists because the employees that serve them are hired from outside the region and food goods for the tourists are imported into the region. In contrast, the budget ecotourists are spatially dispersed and travel each night to a new tourist camp. The budget ecotourists are essential to the economy of Pto. Misahualli. Only inhabitants of Pto. Misahualli are employed in the ecotourism industry, and all food for jungle trips is bought at local stores. Although the budget ecotourists are much more important for the local economy than resort tourists, the infrastructure of the resort ecotourists has a place in promoting the rainforest at the international level. The current ecotourism industry in Napo is sustainable within its own parameters, but the infringement of the oil industry and the small farm colonization on the primary rainforest will ultimately lead to its downfall. (Abstract shortened by UMI.)
Keywords: Geography.